Composite materials for innovative urban farming of alternative food sources (macroalgae and crickets) - Fricke, Anna; Psarianos, Marios; Sabban, Jakob; Fitzner, Maria; Reipsch, Riccardo; Schlüter, Oliver K.; Dreyer, Christian; Vogt, Julia H.-M.; Schreiner, Monika; Baldermann, Susanne (Frontiers in Sustainable Food Systems, 2022)
Facing an inexorable growth of the human population along with substantial environmental changes, the assurance of food security is a major challenge of the present century. To ensure responsible food consumption and production (SDG 12) (UN, 2015), new approaches in the food system are required. Thus, environmentally controlled, sustainable production of alternative food sources are of key interest for both urban agriculture and food research. To face the current challenge of integrating food production systems within existing structures, multidisciplinary discourses are required. Here we bring together novel technologies and indoor farming techniques with the aim of supporting the development of sustainable food production systems. For this purpose, we investigated the feasibility of ten composite materials for their innovative use as structural support in macroalgal cultivation (settlement substrates) and cricket rearing (housing). Considering material resistance, rigidity, and direct material-organism interactions, the bio-based composite polylactic acid (PLA) was identified as a suitable material for joint farming. For macroalgae cultivation, PLA sustained the corrosive cultivation conditions and provided a suitable substrate without affecting the macroalgal physiology or nutritional composition (carotenoids and chlorophylls). For cricket rearing, PLA provided a suitable and recyclable shelter, which was quickly accepted by the animals without any observed harm. In contrast, other common composite components like phenolic resin or aramid were found to be unsuitable due to being harmful for the cultivated organisms or instable towards the applied sterilization procedure. This multidisciplinary study not only provides profound insights in the developing field of urban indoor food production from a new perspective, but also bridges material science and farming approaches to develop new sustainable and resilient food production systems.